ICT and its contribution to economic growth and development in Nigeria - Ekwueme, Godspower Onyekachukwu (Humanities Horizon, 2025)
Nigeria’s economy continues to face structural challenges such as low productivity, inadequate infrastructure, and limited diversification beyond oil. In this context, Information and Communication Technology (ICT) has emerged as a potential driver of economic transformation, offering new opportunities for growth, innovation, and competitiveness. The study population comprised 75 people, including 25 UBA Magadisu staff and 50 ATM cardholders. Using stratified random sampling through a hat-drawn method, 20 staff and 34 customers were selected, following Ndagi’s guideline for small populations. Data was sourced from questionnaires (primary) and internet documents (secondary). The questionnaire’s validity was ensured through supervisor review and reliability tested with a pilot study of 10 GTB staff. Data collection was facilitated by the HR manager, with respondents given five days to complete the instrument. Analysis employed mean scores for Likert responses, percentages for demographics, and chi-square to test significance. The results revealed a fairly balanced gender distribution with slightly more females than males, while the majority of respondents were within the 31–50 years age range. Findings showed strong support for the importance of ICT in Nigeria’s economy, with many agreeing that it contributes to growth and development. ICT awareness was also perceived as high, though doubts remained about its usefulness across all economic sectors. Chi-square analysis confirmed ICT’s significant contribution to Nigeria’s economic development. The study concludes that ICT is a transformative driver of progress in Nigeria, but its full potential can only be realized through enhanced awareness, equitable accessibility, and integration across sectors.